Phenological responsiveness to climate differs among four species of Quercus in North America. (2nd May 2017) - Gerst, Katharine L.; Rossington, Natalie L.; Mazer, Susan J.
Summary: The timing of the seasonal activity of organisms is a tractable indicator of climate change. Many studies in North America have investigated the role of temperature on the onset date of phenological transitions in temperate deciduous trees and found that the onset of leafing and flowering in numerous species has occurred earlier in recent years, apparently in response to higher temperatures in winter and spring. Few studies have examined the climatic and biogeographic drivers of phenological responses in water‐limited ecosystems or explored interspecific variation in responses of phenological metrics other than the timing of onset, such as the periodicity or duration of phenological activity. This study used phenological observations of four species of Quercus contributed to the USA National Phenology Network database from 2009 to 2014 to investigate how responses to climate (temperature and precipitation) and geographic location (latitude, longitude and elevation) varied among two western North American species ( Q. agrifolia and Q. lobata ) and two eastern and central North American species ( Q. alba and Q. rubra ). Within years, in species in the western, water‐limited ecosystems, the phenological phases observed here (bud break, flowers or flower buds) tend to occur intermittently throughout the growing season, and each event is of longer duration than the same phenophases of the temperate‐zone species, rendering a single onset date an incomplete metric with which to track responsiveness or to compare species. By contrast, the eastern/central U.S. species were phenologically more responsive than the western species to spatial and temporal variation in winter, spring, and fall precipitation and maximum temperature. Synthesis . Within and between regions these congeners exhibited a diversity of responses to seasonal temperature and precipitation. This indicates that for predictive model development it is critical to understand how each underlying driver influences species that are adapted to different climatic regimes. These results underscore the value of studying a range of phenological metrics and species from a variety of ecosystems to better predict phenological responses to short‐term variation and to long‐term change in climate. Abstract : Within and between regions, Quercus congeners exhibited a diversity of responses to seasonal temperature and precipitation. To develop predictive phenology models, it is critical to understand how underlying drivers influence species that are adapted to different climatic regimes. These results underscore the value of studying a range of phenological metrics to understand responses to short‐term variation and to long‐term change.